PRASASTI MAYUNGAN, BATURITI, TABANAN - Ida Ayu Wayan Prihandari (Balai Arkeologi Bali, 2014)
Mayungan Inscription was found accidentally by people of Mayungan. Based on research this inscription was issued by The King of Jayapangus and His two queens. It could be said that this inscription is almost complete because it mentions the name of Mayungan as the village that received the inscription. The aims of this study are to know the content of the inscription and Mayungan peoples perception on it. Observation, interview, and literature study on the five plates of the inscription were applied to get the data. The inscription mentions about tax dispute happened in Mayungan. The discovery of the inscription brings positive effect to the peoples behaviour on cultural heritage preservation.Prasasti Mayungan ditemukan secara tidak sengaja oleh masyarakat Mayungan. Prasasti ini dikeluarkan oleh Raja Jayapangus beserta kedua permaisuri beliau, merupakan prasasti lengkap, menyebut nama Desa Mayungan sebagai desa penerima prasasti. Tujuan penelitian adalah untuk mengetahui isi prasasti dan persepsi masyarakat Mayungan atas prasastinya. Metode yang digunakan adalah metode observasi, wawancara, dan studi pustaka, terhadap lima lempeng Prasasti Mayungan. Prasasti ini memuat tentang kasus perpajakan yang terjadi di Desa Mayungan. Temuan Prasasti berdampak positif terhadap perilaku masyarakat dalam penanganan warisan budaya.